Design of a Web-Based Employee Performance Appraisal System at PT PLN Icon Plus Medan Using the Design Thinking Method - Putri Maria Angelina; Hafni; Muhammad Zen (Cattleya Darmaya Fortuna, 2026)
Employee performance appraisal is an important aspect of human resource management that plays a role in improving organizational productivity and effectiveness. PT PLN Icon Plus Medan, as a company engaged in information and communication technology, faces challenges in its employee performance appraisal system, which is still carried out manually and subjectively. This study aims to design and develop a structured web-based employee performance appraisal system using the Analytical Hierarchy Process (AHP) method, the Flutter framework, and Pocketbase as a backend solution. This system is designed to produce more objective, transparent, and accountable assessments through consistent weighted calculations. The results of the study show that by integrating AHP, the system is able to convert subjective assessments into valid numerical data, while the use of Flutter enables the development of a responsive application that is easily accessible to employees and management. Pocketbase provides an efficient backend solution for real-time data management. This system is expected to improve efficiency in the employee performance evaluation process, support more accurate decision-making, and provide a strong foundation for competency development and human resource development policies at PT PLN Icon Plus Medan.